Morquio B disease: a case report - Gholamian, Tara; Chhina, Harpreet; Stockler, Sylvia; Cooper, Anthony (Frontiers in Pediatrics, 2024)
Mucopolysaccharidosis IV type B, or Morquio B Disease (MBD), is an autosomal recessive condition caused by a genetic mutation in the GLB 1 gene coding for β-galactosidase on chromosome 3p22.33. β-galactosidase deficiency can result in two different conditions, GM1 gangliosidosis and MBD, of which MBD has a milder phenotype and presents later in life with β-galactosidekeratan sulphate accumulation in the retina and cartilage. In this case report we discuss a patient with MBD that was diagnosed at the age of 5 after initially presenting with Morquio dystosis multiplex and characteristic x. This included a bell-shaped chest, pectus carinatum, long and hyperextensible limbs, and a short neck and trunk. rRadiographic characteristics findings. at diagnosis included a flat vertebra, hypoplastic odontoid with a stable relationship between C1 and C2, platyspondyly and hip dysplasia. Genetic testing showed the patient to have β-galactosidase deficiency with mutation W273L/N484K on the GLB1 gene. The patient had elevated mucopolyshaccarides in his urine at 18 mg/mmol and had an abnormal band pattern of urine oligosaccharides on electrophoresis. The activity of β-galactosidase in his white blood cells was reduced at 12.3 nmol/hr/mg protein. At diagnosis, the patient did not have issues with gait and ambulation, but his ability to walk progressively deteriorated in his adolescence as a result of ankle, knee, and hip joint instability and pain with and a global decrease in muscle strength. This case report is the first in the literature to provide an in-depth exploration of the orthopedic treatment and follow-up a young adolescent with MBD received in order to provide symptom relief and improve walking ability.